Effect of zoledronic acid on functional outcome in cases of pertrochanteric femoral fractures in elderly patients operated with proximal femoral nailing - Lakhtakia, Pankaj K.; Chaurasia, Amit K.; Singh, Vidyabhushan; Verma, Pradeep K.; Vora, Abhi K.; Shah, Vineet; Dwivedi, Sudhakar (International Journal of Research in Orthopaedics, 2023)
Background: Osteoporosis is a very common problem in geriatric population and postmenopausal women. Zoledronic acid injection is a very convenient and effective treatment option available for osteoporosis. Our study aimed to study the effect of zoledronic acid on functional outcome and fracture related complications in elderly patients with low energy pertrochanteric femoral fractures who were operated with proximal femoral nail. Methods: This was a case control study. Elderly patients who underwent surgery in the form of proximal femoral nailing for low energy pertrochanteric femoral fractures were included. Injection zoledronic acid was given to every alternate patient who underwent surgery. Radiological healing was evaluated at six weekly intervals for six months and then 12 weekly intervals for one year. The Harris hip score was used to measure the functional outcome of the patient. Results: Effective study population consisted of total 49 patients (25 cases and 24 controls). The mean union time in the cases and the control was 8.76±9.12 weeks and 7.04±1.57 weeks respectively. The mean Harris hip score was 86.742±7.55 in the cases and 84.339±11.20 in the control group. The p value was 0.3815. This study concluded that the two groups had no statistically significant difference between functional outcome and fracture related complications. Conclusions: Zoledronic acid in patients admitted for surgery with osteoporotic fracture does not improve the functional outcome of the patients. It does not affect the mortality of the patients.